Synthesis of novel star-shaped molecules based on a pentaerythritol core linked to different heterocyclic systems - Hadeer M. Diab; Ismail A. Abdelhamid; Mostafa E. Salem; Islam Ragab; Magdi E.A. Zaki; Amr M. Abdelmoniem; Ahmed H.M. Elwahy (Results in Chemistry, 2024)
Synthesis of analogs of known active compounds is the most often employed strategy for producing important compounds. The Hantzsch reaction was employed to create new star-shaped compounds with a pentaerythritol core connected to thiazoles, hexahydroacridinediones, decahydropyrimido[4,5-b]quinolones, and tetrahydro[1,2,4]triazolo[5,1-b]quinazoline in this study. The flexible precursor was 4′-((2,2-bis((4-formylphenoxy)methyl)propane-1,3-diyl)bis(oxy))dibenzaldehyde. Under milder reaction conditions, the target compounds were produced with high yields as well as shorter reaction times. The structures of the new compounds were established using elemental analysis and spectral data.